2011
DOI: 10.1108/09513571111133054
|View full text |Cite
|
Sign up to set email alerts
|

Preferences, constraints and work‐lifestyle choices

Abstract: Purpose -Men and women are now being admitted to membership of the major UK professional accountancy bodies in approximately equal numbers. This trend has focused attention on the ways in which professional accountants combine careers and family life, particularly when women have children. Recognising the limitations inherent in the widely-used term "work-life balance" that polarises life and work, this paper instead seeks to consider the "work-lifestyle choices" made by female accountants. Work-lifestyle choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 29 publications
(34 reference statements)
1
22
0
5
Order By: Relevance
“…Gallhofer, et al (2011) observed that, women who worked part-time or had other flexible working arrangement appeared to have made their work-lifestyle choices given preferences for combing motherhood and employment. Structural constraints impacting upon their work-lifestyle choices were experienced by several women who would have preferred to work part-time but could not do so because their employer did not offer this option.…”
Section: The Ability Of the Female Accountant To Balance Their Work Amentioning
confidence: 99%
See 1 more Smart Citation
“…Gallhofer, et al (2011) observed that, women who worked part-time or had other flexible working arrangement appeared to have made their work-lifestyle choices given preferences for combing motherhood and employment. Structural constraints impacting upon their work-lifestyle choices were experienced by several women who would have preferred to work part-time but could not do so because their employer did not offer this option.…”
Section: The Ability Of the Female Accountant To Balance Their Work Amentioning
confidence: 99%
“…For example, Gallhofer, et al (2011) found that where they can female ICAS members often prefer to work part-time rather than full-time in order to combine work and home lifestyles effectively.…”
Section: The Ability Of the Female Accountant To Balance Their Work Amentioning
confidence: 99%
“…Neste contexto, os estudos têm sugerido que as mulheres continuam a enfrentar discriminação em função do género (Haynes, 2008a(Haynes, , 2008bLyonette e Crompton, 2008), ou raça (McNicholas, Humphries e Gallhofer, 2004;Kamla, 2012), e que a opção pela maternidade e por dedicar mais tempo à família pode influenciar negativamente a sua progressão na carreira (Gallhofer et al, 2011;Dambrin e Lambert, 2012). Os estudos sugerem ainda que as práticas nas maiores empresas de auditoria reproduzem a dominação masculina (Kornberger, Carter e Ross-Smith, 2010), ou que o género é uma variável importante na explicação das diferenças salariais existentes na profissão de contabilista (Lyonette e Crompton, 2008).…”
Section: Contabilidade E Génerounclassified
“…Nos últimos anos, a investigação tem abordado questões como o impacto dos papéis de género nas opções de carreira e nas escolhas de estilo de vida e trabalho das mulheres (Gallhofer et al, 2011;Lupu, 2012), da progressão das mulheres na carreira contabilística (Dambrin e Lambert, 2012), do impacto que a presença de mulheres nos níveis hierárquicos superiores de gestão tem nos resultados das empresas (Francoeur, Labelle e Sinclair-Desgagné, 2008), e do papel do género em relação à gestão estratégica e aos processos contabilísticos existentes nas organizações (Parker, 2008).…”
Section: Contabilidade E Génerounclassified
See 1 more Smart Citation